Challenges to conducting research on oral health with older adults living in long-term care facilities - Thayse Mayra Chaves Ramos; Álvaro Augusto da Silva Alves; Thais Andrade Apolinário; Flávia Fonseca de Toledo; Viviane Elisângela Gomes; Kevan Guilherme Nóbrega Barbosa; Aline Araújo Sampaio; Raquel Conceição Ferreira (BMC, 2024)
Abstract Background The challenges to conducting oral health studies involving older people in long-term care facilities (LTCFs) must be debated. Objective This study aimed to investigate researchers' perceptions and experiences while conducting an epidemiological survey on oral health among older individuals residing in LTCFs. Methods A qualitative study was conducted involving six researchers who utilized field diaries to record their impressions during data collection through interviews (older individuals (or their proxies), caregivers, and LTCF coordinators) and oral examinations of the older people participants. Additionally, researchers responded to open-ended questions about their experiences. The collected material was subjected to content analysis by two researchers. Results The themes that emerged from the analysis were institutional context, aspects affecting the operationalization of the study, and data collection oriented by the clinical-functional profile of the older people. According to the researchers' perceptions, LTCF coordinators demonstrated concern for the study's benefits for older adults and the preservation of institutional routines during the research process. Caregivers emerged as vital sources of information, guiding researchers in navigating the challenges posed by the physical and mental complexities of the older people participants, necessitating empathy, sensitivity, and attentive listening from the researchers. The organization of materials and a streamlined data collection process proved essential for optimizing time efficiency and reducing stress for participants and researchers. Conclusion The researchers recognized the important role played by LTCF coordinators and formal caregivers, underscoring the significance of empathetic methodologies and streamlined data collection processes in mitigating the challenges inherent to research conducted within LTCFs.